Automated recognition of thinking orders in secondary school student writings. (2nd January 2017) - Hu, Xiao
ABSTRACT: Despite the rapid development in the area of learning analytics (LA), there is comparatively little focused towards the secondary level of education. This ongoing work presents the latest developed function of Wikiglass, an LA tool designed for automatically recognising, aggregating, and visualising levels of thinking orders in student collaborative writing. Three levels of thinking orders were defined based on frameworks in writing assessment and an adapted Bloom's taxonomy of cognitive domains. Text categorisation models were constructed and evaluated using machine learning and natural language processing techniques. The best performing model was then integrated into Wikiglass, with visualisations in different modes and scopes (i.e., class, group, individual). Currently being used in classrooms, Wikiglass is expected to assist teachers in identifying at-risk individuals and groups, refining assessment rubrics, and selecting example sentences as teaching materials, as well as to facilitate students in self-monitoring and reflection.